Sorption and Release of Organics by Primary, Anaerobic, and Aerobic Activated Sludge Mixed with Raw Municipal Wastewater - Modin, Oskar (PLoS One, 2015)
New activated sludge processes that utilize sorption as a major mechanism for organics removal are being developed to maximize energy recovery from wastewater organics, or as enhanced primary treatment technologies. To model and optimize sorption-based activated sludge processes, further knowledge about sorption of organics onto sludge is needed. This study compared primary-, anaerobic-, and aerobic activated sludge as sorbents, determined sorption capacity and kinetics, and investigated some characteristics of the organics being sorbed. Batch sorption assays were carried out without aeration at a mixing velocity of 200 rpm. Only aerobic activated sludge showed net sorption of organics. Sorption of dissolved organics occurred by a near-instantaneous sorption event followed by a slower process that obeyed 1(st) order kinetics. Sorption of particulates also followed 1(st) order kinetics but there was no instantaneous sorption event; instead there was a release of particles upon mixing. The 5-min sorption capacity of activated sludge was 6.5±10.8 mg total organic carbon (TOC) per g volatile suspend solids (VSS) for particulate organics and 5.0±4.7 mgTOC/gVSS for dissolved organics. The observed instantaneous sorption appeared to be mainly due to organics larger than 20 kDa in size being sorbed, although molecules with a size of about 200 Da with strong UV absorbance at 215–230 nm were also rapidly removed.